Determining the Risk Factors for Anastomotic Stricture Development after Esophageal Atresia Repair: Results from the Turkish Esophageal Atresia Registry - Öztorun, Can İhsan; Ulukaya Durakbaşa, Çiğdem; Soyer, Tutku; Özcan, Coşkun; Fırıncı, Binali; Demirel, Berat Dilek; Çiftçi, İlhan; Parlak, Ayşe; Öztan, Mustafa Onur; Göllü Bahadır, Gülnur; Akkoyun, İbrahim; Karaman, Ayşe; Gül, Cengiz; Şalcı, Gül; İlhan, Hüseyin; Oral, Akgün; Özcan, Rahşan; Özaydın, Seyithan; Kılıç, Şeref Selçuk; Kıyan, Gürsu; Erdem, Ali Onur; Uzunlu, Osman; Yıldız, Abdullah; Özçakır, Esra; Ertürk, Nazile; Erginel, Başak; Öztaş, Tülin; Atıcı, Ahmet; Mert, Mehmet; Samsum, Hakan; Özen, Mehmet Ali; Aydın, Emrah; Sancar, Serpil (European Journal of Pediatric Surgery, 2024)
Introduction Anastomotic stricture (AS) is the second most common complication after esophageal atresia (EA) repair. We aimed to evaluate the data in the Turkish Esophageal Atresia Registry to determine the risk factors for AS development after EA repair in a large national cohort of patients.Methods The data between 2015 and 2021 were evaluated. Patients were enrolled into two groups according to the occurrence of AS. Patients with AS (AS group) and without AS (non-AS group) were compared according to demographic and operative features, postoperative intubation status, and postoperative complications, such as anastomotic leaks, fistula recanalization, and the presence of gastroesophageal reflux (GER). A multivariable logistic regression analysis was performed to define the risk factors for the development of AS after EA repair.Results Among the 713 cases, 144 patients (20.19%) were enrolled into the AS group and 569 (79.81%) in the non-AS group. The multivariable logistic regression showed that, being a term baby (odds ratio [OR]: 1.706; p = 0.006), having a birth weight over 2,500 g (OR: 1.72; p = 0.006), presence of GER (OR: 5.267; p < 0.001), or having a recurrent tracheoesophageal fistula (TEF, OR: 4.363; p = 0.006) were the risk factors for the development of AS.Conclusions The results of our national registry demonstrate that 20% of EA patients developed AS within their first year of life. In patients with early primary anastomosis, birth weight greater than 2,500 g and presence of GER were risk factors for developing AS. When patients with delayed anastomosis were included, in addition to the previous risk factors, being a term baby, and having recurrent TEF also became risk factors.Level of Evidence III.
Keywords: esophageal atresia; tracheoesophageal fistula; anastomotic strictures; risk factors